A Study on Drought and Migration of Agricultural Labourers And Farmers: - Reference to Dumberpali Panchayat, Sohela Block (Odisha) - Rajib Kumar Barik,; Dr. Pratima Bais, (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
Drought is a natural disaster, which influences all living and non-living organisms. Its effect all segments the society. Agriculture is highly affected due to occurrence of drought. Low rainfall makes the land dry and reduces the productivity and production and also income of the farmers, for them agriculture is the primary source of livelihoods. Agriculture labourers also extremely influence because of drought. The landless farmer‟s uses migration a coping strategy to face the challenges and try to find out new occupation for survive. The small and marginal farmers uses same strategy to face the challenges occurred due to drought. This article discussed about the impact of drought on migration in the study areas.